1988
DOI: 10.1177/096032718800700610
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Feeding of a Dilute Antiseptic Solution (Chlorhexidine 0.05% with Cetrimide 1%) to Five Babies

Abstract: Five normal newborn breast fed babies were accidentally fed a dilute antiseptic solution (chlorhexidine 0.05% with cetrimide 1%) in place of sterile water, developing caustic burns of the lips, mouth and tongue within minutes; one baby became quite severely ill due to acute pulmonary oedema, but all survived without sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Disinfectants and surfactants are used widely as an active ingredient in household and personal care products like dishwashing and laundry liquids, bleach and cosmetics that are commercially available in supermarkets. These products are daily necessities and accidental ingestion by old people or young children seems to have occurred more frequently than previously reported (Berkel and Wolff, ; Ohta et al , ; Wilson and Burr, ; Hironaga, ; Ichihara et al , ; Nagai et al , ; Mucklow, ; Balit et al , ; Ishigami et al , ; Kudo et al , ; Usui et al , ; Massano et al , ; Hirata and Kurokawa, ; Adelson and Sunshine, ; Hitosugi et al , ; Akutsu et al , ). The annual report of poisoning, required from 1998 to 2009 by The Japan Poison Information Center (), showed that household products were the highest poison hazards and their percentage of total causative materials was over than 64% every year.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Disinfectants and surfactants are used widely as an active ingredient in household and personal care products like dishwashing and laundry liquids, bleach and cosmetics that are commercially available in supermarkets. These products are daily necessities and accidental ingestion by old people or young children seems to have occurred more frequently than previously reported (Berkel and Wolff, ; Ohta et al , ; Wilson and Burr, ; Hironaga, ; Ichihara et al , ; Nagai et al , ; Mucklow, ; Balit et al , ; Ishigami et al , ; Kudo et al , ; Usui et al , ; Massano et al , ; Hirata and Kurokawa, ; Adelson and Sunshine, ; Hitosugi et al , ; Akutsu et al , ). The annual report of poisoning, required from 1998 to 2009 by The Japan Poison Information Center (), showed that household products were the highest poison hazards and their percentage of total causative materials was over than 64% every year.…”
Section: Discussionmentioning
confidence: 89%
“…Through utilizing our previously developed methods, concentrations of BZK, BZT and CHX in blood, lung, liver and kidney in rats were determined following a dose of 15 mg kg −1 intravascularly or 250 and 1250 mg kg −1 orally. Lung, liver and kidney were selected as tissue samples because these organs have been reported as affected tissues in human poisoning cases and in animal experiments (Xue et al , 2004a, b; Tiess and Nagel, ; Mucklow, ; Chow et al , ). The individual levels in blood and tissues at 24 h after administration were plotted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of pulmonary and tongue edema and oral ulcers in infants who received 0.05% CHX orally after the antiseptic agent was mistaken for sterile water have been reported 30 . After developing respiratory distress syndrome, an elderly patient died due to ingestion of 10 g of CHX in a 200 mL solution 31 .…”
Section: Discussionmentioning
confidence: 99%
“…31,33 There are case series that reported chlorhexidine accidental intake, and side effects resolved once exposure was interrupted. 34,35 …”
Section: Chlorhexidine Adverse Reactionsmentioning
confidence: 99%